2020
DOI: 10.1108/ijsms-06-2019-0066
|View full text |Cite
|
Sign up to set email alerts
|

Motives to engage with sports brands on Facebook and Instagram–The case of a Portuguese football club

Abstract: PurposeSocial network sites are key marketing tools that allow brands to connect and engage with consumers. However, there is still a lack of evidence of their value for football brands. This research aims to understand the motivations for fans to engage with their favourite football brands on Facebook and Instagram.Design/methodology/approachAn online survey was performed, resulting in 214 valid responses. As the social media strategy followed by the football brand analysed was built around games, the authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 81 publications
2
15
0
6
Order By: Relevance
“…To understand what can motivate the fans to engage with the football club they support on the social media, Ferreira et al (2019) publish a study for this purpose as they used an online survey to collect the data from FC Porto (Portuguese football club) fans and they found that the entertainment content and searching for information were the two main things people do to engage with their favorite football club on the social media. Similar results showed in the study done by Machado et al (2020) which included more sample size and covered many Portuguese football clubs' fans and social media accounts.…”
Section: Kriemadis Et Al (2010) Published a Paper Which Was A Compari...supporting
confidence: 87%
“…To understand what can motivate the fans to engage with the football club they support on the social media, Ferreira et al (2019) publish a study for this purpose as they used an online survey to collect the data from FC Porto (Portuguese football club) fans and they found that the entertainment content and searching for information were the two main things people do to engage with their favorite football club on the social media. Similar results showed in the study done by Machado et al (2020) which included more sample size and covered many Portuguese football clubs' fans and social media accounts.…”
Section: Kriemadis Et Al (2010) Published a Paper Which Was A Compari...supporting
confidence: 87%
“…A lo largo de los años, la gestión de estas plataformas digitales por parte de las organizaciones deportivas han sido objeto de estudio. Desde equipos y clubes deportivos (ACHEN, 2019;JORDAN;UPRIGHT;FORSYTHE, 2017;MACHADO et al, 2020; a federaciones internacionales (BURSON COHN & WOLFE SPORTS, 2021;GINESTA, 2009;VILANOVA, 2009;WINAND et al, 2019) o incluso deportistas (HAYES, 2020;SHARPE;MOUNTIFIELD;FILO, 2020;WITKEMPER;LIM;WALDBURGER, 2012).…”
Section: Enfoques De Gestión En La Comunicación Digital En Las Organi...unclassified
“…Coelho et al (2016) highlight that more intense interactions between customers, companies and clubs or players are possible on Instagram. For the fans, entertainment, rewards, social influence and searching for information are the main motivations to interact with sports entities on Facebook, whereas only the first three motivations are important on Instagram (Machado et al, 2020). Oppositely, Twitter is less attractive for advertisements, due to its character limitation and the lower number of total users.…”
Section: Factors Affecting the Value Of Advertisementsmentioning
confidence: 99%